The Effectiveness of Digital Module as a Guide in the Al-Qur’an Study - Rohman, Baeti; Ayuningrum, Desy; Jarudin (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to develop a digital module as a guide in the study of the Qur’an. This study uses a mixed-method with a quantitative approach. Using a questionnaire instrument with a Likert scale. The instrument validation was carried out by a team of experts, namely material, design, and learning media experts who were competent in their respective fields. Feasibility test results are based on expert validation that an average value of 93% means that the resulting product is suitable for use, while the effectiveness test results are based on field test results with pre-test and post-test instruments. The results have increased by 1.3 units, meaning this product is effective as a guide in studying the Qur’an. Based on the feasibility test and effectiveness test, it can be concluded that the digital module was very effective as a guide in studying the Qur’an.